Proapoptotic Effect Annona muricata Leaf Extract on HT29 Colon Cancer Cell - Abdullah Kshidan M (Journal of Global Pharma Technology, 2019)
The occurrence of colon cancer has rapidly increased across the globe and currently ranks among the third highest disease difficult to treat with drugs. Therefore, there is need for the use of natural compound in its treatment. Graviola (Annona muricata) leaf has several anti-apoptosis and proliferation active compoundswhich make the colon cancer induced by constitutive activation of NF-KB. This experiment therefore, utilized leaves of Annona muricataextracts obtained from Materia Medica in Batu. The leaves were found to inhibit cell proliferation by MTT assay and also induced apoptosis by Annexin V and Flowcytometry with the ability to inhibit NF-KB expression present in nucleus cells. The crude extract of Graviola leaves inhibits cell proliferation and increases apoptosis and through the inhibition of NF-KB pathway. It also increases the apoptosis of HT29 cell.